Giant cross-Kerr nonlinearity in a four-level Y-type atomic system - Phu, Nguyen Van; Bang, Nguyen Huy; Le, Doai Van (Photonics Letters of Poland, 2021)
The analytical expression for the group index in a degenerated three-level lambda-type atomic system is derived as a function of the parameters of laser fields and external magnetic field. The influence of the external magnetic field on the group index is investigated. It is shown that by changing the magnitude or sign of the external magnetic field, the transparency window with normal dispersion switches to enhanced absorption with anomalous dispersion at the line center and hence the light propagation can be converted between subluminal and superluminal modes. Full Text: PDF References R. W. Boyd, "Slow and fast light: fundamentals and applications", J. Mod. Opt. 56 (2009) 1908-1915 CrossRef K.J. Boller, A. Imamoglu, S.E. Harris, "Observation of electromagnetically induced transparency", Phys. Rev. Lett. 66 (1991) 2593. CrossRef A. Lezama, S. Barreiro, and A. M. Akulshin, "Electromagnetically induced absorption", Phys. Rev. A 59 (1999) 4732-4735. CrossRef L. V. Hau, S. E. Harris, Z. Dutton, C. H. Bejroozi, "Light speed reduction to 17 metres per second in an ultracold atomic gas", Nature 397, 594 (1999) CrossRef L. J. Wang, A. Kuzmich, and A. Dogariu, "Gain-assisted superluminal light propagation", Nature 406 (6793), 277-279 (2000) CrossRef A. V. Turukhin, V. S. Sudarshanam, M. S. Shahriar, J. A. Musser, B. S. Ham, P. R. Hammer, "Observation of Ultraslow and Stored Light Pulses in a Solid", Phys. Rev. Lett. 88, 023602 (2002). CrossRef K. Bencheikh, E. Baldit, S. Briaudeau, P. Monnier, J. A. Levenson, and G. Mélin, "Slow light propagation in a ring erbium-doped fiber", Opt. Express 18 (25), 25642-25648 (2010). CrossRef E. E. Mikhailov, V. A. Sautenkov, I. Novikova, G. R. Welch, "Large negative and positive delay of optical pulses in coherently prepared dense Rb vapor with buffer gas", Phys. Rev. A 69, 063808 (2004). CrossRef E. E. Mikhailov, V. A. Sautenkov, Y. V. Rostovtsev, G.R. Welch, "Absorption resonance and large negative delay in rubidium vapor with a buffer gas", J. Opt. Soc. Am. B 21, 425 (2004). CrossRef A. M Akulshin and R. J McLean, "Fast light in atomic media", J. Opt. 12 (2010) 104001. CrossRef Vineet Bharti, Vasant Natarajan, "Sub- and super-luminal light propagation using a Rydberg state", Opt. Comm. 392 (2017) 180-184. CrossRef N.T. Anh, L.V. Doai, D.H. Son, and N.H. Bang, "Manipulating multi-frequency light in a five-level cascade EIT medium under Doppler broadening", Optik 171 (2018) 721-727. CrossRef N.T. Anh, L.V. Doai, and N.H. Bang, "Manipulating multi-frequency light in a five-level cascade-type atomic medium associated with giant self-Kerr nonlinearity", J. Opt. Soc. Am. B 35 (2018) 1233. CrossRef N.H. Bang, L.N.M. Anh, N.T. Dung and L.V. Doai, "Comparative Study of Light Manipulation in Three-Level Systems Via Spontaneously Generated Coherence and Relative Phase of Laser Fields*", Commun. Theor. Phys. 71 (2019) 947-954. CrossRef L.V. Doai, "The effect of giant Kerr nonlinearity on group velocity in a six-level inverted-Y atomic system", Physica Scripta 95 (2020) 035104 (7pp). CrossRef P. Kaur and A. Wasan, "Effect of magnetic field on the optical properties of an inhomogeneously broadened multilevel Λ-system in Rb vapor", Eur. Phys. J. D 71 (2017) 78. CrossRef H. Cheng, H. -M. Wang, S. -S. Zhang, P. -P. Xin, J. Luo and H. -P. Liu, "Electromagnetically induced transparency of 87Rb in a buffer gas cell with magnetic field", J. Phys. B: At. Mol. Opt. Phys. 50 (2017) 095401. CrossRef C. Mishra, A. Chakraborty, A. Srivastava, S. K. Tiwari, S. P. Ram, V. B. Tiwari and S. R. Mishr, "lectromagnetically induced transparency in Λ-systems of 87Rb atom in magnetic field", J. Mod. Opt. 65 (2018) 2269-2277. CrossRef S. H. Asadpour, H. R. Hamedi and H. R. Soleimani, "Slow light propagation and bistable switching in a graphene under an external magnetic field", Laser Phys. Lett. 12 (2015) 045202. CrossRef R. Karimi, S. H. Asadpour, S. Batebi and h. R. Soleimani, "Manipulation of pulse propagation in a four-level quantum system via an elliptically polarized light in the presence of external magnetic field", Mod. Phys. Lett. B 29 (2015) 1550185. CrossRef